Modiolus modiolus Linnaeus 1758 - Ockelmann, Kurt W.; Cedhagen, Tomas (Zenodo, 2019)
Modiolus modiolus (Linnaeus, 1758) DENMARK • Kattegat, E of Fladen, Kanonbaaden Hauch, stn 474; 23 Jul. 1886; C.G.Joh. Petersen leg.; NHMD • Kattegat, Kanonbaaden Hauch, stn 286; 7 m depth; 24 Jun. 1885; C.G.Joh. Petersen leg.; NHMD • Kattegat, off Fornaes lighthouse, Kanonbaaden Hauch, stn 333; 20 m depth; 24 Jun. 1885; C.G.Joh. Petersen leg.; sand, mud; NHMD • Kattegat, Trindelen, Kanonbaaden Hauch, stn 29; 28 m depth; 9 Aug. 1884; C.G.Joh. Petersen leg.; gravel; NHMD. Published as part of Ockelmann, Kurt W. & Cedhagen, Tomas, 2019, Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak, pp. 1-13 in European Journal of Taxonomy 556 on page 2, DOI:10.5852/ejt.2019.556, http://zenodo.org/record/3475433